Tantangan dan Solusi Pengembangan Ar-Rahn BSI KC Gresik Kartini - Nugraha, Raniah Tasya; Lilik Rahmawati (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2022)
Background. The community needs a source of financing that is fast, easy, safe and in accordance with sharia. BSI opens sharia gold pawn services (rahn) with various internal and external challenges.Aim. This study aims to examine the real challenges faced by BSI in the development of sharia gold pawning (rahn) and their solutions.Methods. The researcher used a qualitative research design with a phenomenological study paradigm. The data were collected through unstructured interviews, documentation, and observation. Participants were selected purposively based on the emic perspective. The research data were analyzed using a phenomenological data analysis model.Results. In rahn, there is no term "confiscation" by the recipient of the pawn or pawnee (murtahin) of the pawned gold (marhun), there is a rescheduling mechanism for the redemption of marhun, the gold owner who pawns the gold (rahin) has a great opportunity to maintain and preserve the value of the investment inherent in the gold. In the case of debt (marhun bih) being paid or marhun failing to redeem, rahin does not lose because it still receives the remaining proceeds from selling marhun after deducting the value of marhun bih. Unless the market price of gold falls at that time, rahin will not lose, even if the price of gold on the market goes up, because marhun is priced higher than the initial price of buying gold. As a solution, it is time for the promotion of rahn BSI to be oriented towards public education. Education will make the public realize that rahn is the best choice for pawning gold for Muslims who adhere to sharia principles in worship practices, sharia principles in business.